Implementation of Discovery Learning Model to Improve Learning Achievement in Fiqh Learning at MTs Terpadu Yajamila Dasan Tapen - Muknin (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to improve student learning achievement in fiqh learning using the Discovery learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Discovery learning model can improve student learning achievement in fiqh learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Thus, the use of the Discovery learning model can be used as an alternative to improve student learning achievement in fiqh learning.